(untitled) (Al-Qamar, 2018)
Deviating from the mainstream interpretation of Islam, Ghulām Ahmad (1835-1908) of Qādiān, India claimed to be a prophet and founded Ahmadī or Qādiānī Jamāʻat. After his demise his followers were divided into two groups: Lāhorī Group and Qādiaānī Group. Lāhorī Group was headed by Mawlvī Muhammad ʻAlī Lāhorī and Qādiaānī Group was commanded by Bashīr-ud-Dīn Meḥmood, son of Mirzā Qādiānī. Qādiaānī Group remained adhered to the Prophethood of Mirzā Qādiānī. This group organized a system and a complete network to disseminate the ideas of Mirzā Qādiānī. The present article unfolds Qādiaānī Jamāʻat network that how they are spreading their message across the globe.